Environmental performance of aquaculture in Rondônia state, Brazil - BORGES, AURELIO FERREIRA (Revista Ceres, 2015)
The objective of this study was to analyze the environmental performance of aquaculture in the city of Colorado do Oeste, Rondônia State, Brazil. Fifteen fish farmers were interviewed. For data collection, structured interviews were carried out, using a questionnaire based on information supplied by the United Nations Food and Agriculture Organization (FAO). The questionnaire considered 12 items, organized into three main topics: a) social and legal standards b) environmental standards c) standards of food safety and hygiene. Aquaculture in the city of Colorado do Oeste, Rondônia presents two fish production systems: extensive and semi-intensive. In the semi-intensive system, stocking rate was one fish per m3, on average; tambaqui (Colossoma macropomum), tilapias (Oreochromis spp.), pirarucu (Arapaima gigas) and pintado (Pseudoplatystoma spp.) were the species farmed at the largest number. The rate of water renewal was due to the greater availability of natural food in this system. Water renewal was constant in the ponds (1,500 liters per minute). In the semi-intensive system using dug ponds, alevins were stocked and fed during the entire rearing time with natural and exogenous food. The extensive system relied on the natural production of the pond, with stocking density limited by the production of natural food. The little renewal of water made the cultivation tank itself acted as a decantation lake, with the occurrence of oxidation and sedimentation of residual organic matter, consisting of feces, debris and organic fertilizer. Production of reduced effluent volume took place in the extensive system, compared to the cultivation area. In addition, there was high water turbidity, caused by high concentration of planktonic organisms, and low concentrations of dissolved oxygen in the water. Data showed that nine estates of the interviewed fish farmers had critical environmental performance (less than 30.0%). Six estates of fish farmers had bad environmental performance (between 30.0 and 50.0%) (Coefficient of sustentainability = green square x 100 ÷ Total Questions less the yellow squares).